2023
DOI: 10.26434/chemrxiv-2023-tbvsv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlocking Tertiary Acids for Metallaphotoredox C(sp2)-C(sp3) Decarboxylative Cross-Couplings

Abstract: Dual nickel photoredox catalysis conditions have been developed for the decarboxylative cross-coupling of aryl halides and carboxylic acids containing fully substituted alpha carbons, a valuable but challenging substrate class for C(sp2)–C(sp3) bond-forming reactions. High-throughput experimentation identified Ni(TMHD)2 as the optimal precatalyst for this reaction in contrast to the nickel-bipyridyl complexes typically employed in decarboxylative couplings, which predominantly furnished undesired C–O products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the final optimized conditions, the amount of BINAP could be reduced to 5 mol% along with 25 mol % Ni (Table 1, entry 14 and 15). Basic control studies confirmed the essential nature of the Ni, Ag, BINAP, and pyridine additives as well as electricity (Table 1, entries [16][17][18][19][20]. The final set of conditions are as practically trivial to setup as our previous disclosure (dump and stir) with no precautions taken to remove air or moisture.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…In the final optimized conditions, the amount of BINAP could be reduced to 5 mol% along with 25 mol % Ni (Table 1, entry 14 and 15). Basic control studies confirmed the essential nature of the Ni, Ag, BINAP, and pyridine additives as well as electricity (Table 1, entries [16][17][18][19][20]. The final set of conditions are as practically trivial to setup as our previous disclosure (dump and stir) with no precautions taken to remove air or moisture.…”
mentioning
confidence: 62%
“…[11][12][13][14] Whereas the scope of such couplings is broad when primary and secondary acids and their redoxactive esters (RAEs) are employed, extending that reactivity to tertiary acids has been a vexing problem. [15][16][17][18] For instance, the simple coupling of RAE/acid 1a-b with pyrimidine 2 fails under the most modern of conditions (chemical, photochemical, electrochemical), delivering at most 9% yield. Although the published scope of these methods generally tolerates numerous types of arenes, the only competent alkyl coupling partners involve systems that form radicals which are part of a strained ring system or stabilized by the presence of an -heteroatom (as listed in Figure 1B).…”
mentioning
confidence: 99%
See 3 more Smart Citations